1992
DOI: 10.1139/v92-196
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine in mineral soil: the analytical chemistry of speciation

Abstract: The HPLC–microfiltration method previously described for determining atrazine and hydroxyatrazine species in organic soil has been adapted to a mineral soil. The method was able to monitor atrazine concentrations of less than 1.0 × 10−6 M, which is over 40 times lower than the atrazine concentrations measured in the earlier organic soil experiments. During kinetics.experiments, it also monitored four free and sorbed chemical species instead of only one. Measurements were obtained with much better accuracy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…The reverse reaction must increase in rate similarly. Note that this work did not cover the effect of temperature on the sorption capacity (θ C ) which was assumed to be a constant value (0.397 × 10 -6 mol g -1 ) in all cases (Gamble and Khan, 1990;Gamble and Ismaily, 1992). But, this parameter could vary slightly as a function of temperature.…”
Section: Labile Sorption As Shown Inmentioning
confidence: 99%
“…The reverse reaction must increase in rate similarly. Note that this work did not cover the effect of temperature on the sorption capacity (θ C ) which was assumed to be a constant value (0.397 × 10 -6 mol g -1 ) in all cases (Gamble and Khan, 1990;Gamble and Ismaily, 1992). But, this parameter could vary slightly as a function of temperature.…”
Section: Labile Sorption As Shown Inmentioning
confidence: 99%
“…An analytical chemical method similar to that described earlier for an organic soil has been developed for this purpose (2,3). It has been shown that organic matter dominates pesticide interactions with soils, and carboxyl groups have been identified as being important in these interactions (3, .…”
Section: Introductionmentioning
confidence: 99%
“…Proof of concept has been published for the experimentally supported theory that reveals the kinetics and mechanisms of pesticides in soil and water [1][2][3][4][5][6][7][8][9]. For a soil immersed in a pesticide solution, the starting point was the answer to a critical question.…”
Section: What Has Been Donementioning
confidence: 99%
“…This problem was solved by adding a new HPLC (High Pressure Liquid Chromatography) method to the analytical chemistry methods already available [1,6,7]. In brief, a sample consisted of soil slurried in a pesticide solution.…”
Section: What Has Been Donementioning
confidence: 99%
See 1 more Smart Citation